Relationship between resilience and treatment continuity in opioid use disorder patients - Şahiner, Şafak Yalçın; Asut, Gonca; Şahiner, İsmail Volkan (Journal of Dependence, 2022)
Objective: Opioid addiction is a disease with low remission rates that is difficult to treat in our country and in the World. One of the main reasons for the low remission rates is the difficulties in maintaining the continuation of the treatment. Resilience is one of the factors that determine people’s reactions in difficult situations. In our study, we aimed to examine the relationship between psychological resilience and some sociodemographic characteristics with treatment continuation in patients with opioid use disorder. Method: A sociodemographic data form and a psychological resilience scale for adults were given to 260 patients who were admitted to Ankara Alcohol Substance Treatment and Education Center (AMATEM) for the first time whose urine analysis results were positive. The patients included in the study were followed up for 6 months by urinalysis and psychiatric interviews. Results: A total of 260 patients, 243 men and 17 women, were included in the study. While 61 patients did not come after the first application, 70 patients came to regular follow-up for 6 months. Psychological resilience was found significantly lower in patients who received disciplinary punishment at school, who did not work, who were previously in prison, who has family history about alcohol or drug use. Psychological resilience of the patients who continued follow-up was found higher. Conclusion: Treatment continuation of is one of the important factors affecting remission in opioid addiction. Factors such as family history, prison history, unemployment, resilience, and social resources can affect the continuation of treatment.